2007
DOI: 10.1521/suli.2007.37.4.475
|View full text |Cite
|
Sign up to set email alerts
|

Heroin Addicts Reporting Previous Heroin Overdoses Also Report Suicide Attempts

Abstract: Nonfatal heroin overdoses and suicide attempts are both common among heroin addicts, but there is limited knowledge about the association between them. The sample in the present study consisted of 149 regular heroin users in Malmö, Sweden. Out of these 98 had taken an unintentional heroin overdose at some time and 51 had made at least one attempt to commit suicide (but not using heroin). Suicide attempts were significantly more common among those who had taken unintentional overdoses as compared with those who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 24 publications
2
15
0
4
Order By: Relevance
“…39 However, some argue that accidental drug overdose has also been counted as suicide. 40 Descriptive studies in China found that drug users had lower self-esteem than the normal population. 41,42 Generally, low self-esteem has been linked to anger, aggression, poor problem-solving skills, impulsiveness, increased substance abuse, more HIV risk-taking behaviors, depression, and suicide.…”
Section: Psychological Problems Need To Emphasis Family Support and Dmentioning
confidence: 99%
“…39 However, some argue that accidental drug overdose has also been counted as suicide. 40 Descriptive studies in China found that drug users had lower self-esteem than the normal population. 41,42 Generally, low self-esteem has been linked to anger, aggression, poor problem-solving skills, impulsiveness, increased substance abuse, more HIV risk-taking behaviors, depression, and suicide.…”
Section: Psychological Problems Need To Emphasis Family Support and Dmentioning
confidence: 99%
“…9,10 Psychiatric risk factors associated with OD in substance users include depression 11 and increased impulsivity. 12 Likewise, a history of a suicide attempt has also been associated with history of OD in substance users 5,13,14 although many of the studies that examined this relationship did not evaluate for differences related to the intentionality of the OD. 5,12,13 …”
Section: Introductionmentioning
confidence: 99%
“…Recent research has focused on various psychological risk factors for overdose, such as depression, posttraumatic stress disorder, and suicidal behaviour (Bohnert, Roeder, & Ilgen, 2011; Bradvik, Frank, Hulenvik, Medvedeo, & Berglund, 2007; Havens et al, 2011; Pabayo, Alcantara, Kawachi, Wood, & Kerr, 2013; Tobin & Latkin, 2003b). While evidence suggests that experiences of childhood trauma are strong predictors of depression and suicide in IDU (Marshall, Galea, Wood, & Kerr, 2013; Walton et al, 2011), childhood trauma has received little attention as a risk factor for non-fatal overdose, despite being reported at a high rate within IDU and at-risk (i.e.…”
Section: Introductionmentioning
confidence: 99%